Level of political and voting rights awareness among degree students of UiTM Kota Samarahan / Junainah Maon and Norman Jukie - Maon, Junainah; Jukie, Norman (2010)
By 2020, Malaysia hopes to become a developed nation. Consistent with these goals, various efforts have been and are being made for ensure that these aspirations are achieved. Among the government have urged people Malaysia united efforts to ensure that Vision 2020 is achieved. The target groups of students who successfully serve by Vision 2020.There is no doubt that the roles and responsibilities of a student very large. By the application of moral values should be started from scratch again. Among the values of the mean is like having a character leadership, honesty, responsibility and prudence high. Hence, students as generation of successors to build self- esteem in terms of personal, mental, science and good for people to become a dynamic and distinctive.